Effectiveness of a guided risk management strategy on the knowledge and attitude regarding the prevention of metabolic syndrome among adolescents - Paul, Asha; Molly, John (International Journal Of Community Medicine And Public Health, 2017)
Background: Lifestyle diseases are spreading very rapidly in all over countries. With a view to assess the risk factors for metabolic syndrome and to assess the effectiveness of a guided risk management strategy on knowledge and attitude regarding the prevention of metabolic syndrome among adolescents, a pre experimental one group pre-test post-test design was used on plus two students. Method: They were screened by using a non-invasive risk assessment method and eighty three students were selected as samples by purposive sampling technique. Pre-test was conducted using structured knowledge questionnaire and attitude scale and guided risk management strategy was administered. Post-test was done after seven days. Result: The Results showed that guided risk management strategy was effective in terms of change in knowledge and attitude scores. There was an association between pre-test level of knowledge with education and occupation of mother and association between pre-test level of attitude with occupation of father and mother. Conclusion: The present study showed that 39% of students had the risk factors for metabolic syndrome. The guided risk management strategy was effective in improving the knowledge and attitude of adolescents regarding the prevention of metabolic syndrome.